Thousand cankers disease in Juglans: Optimizing sampling and identification procedures for the vector Pityophthorus juglandis, and the causal agent Geosmithia morbida - Moricca, Salvatore; Bracalini, Matteo; Benigno, Alessandra; Ghelardini, Luisa; Furtado, Edson Luiz [UNESP]; Marino, Celso Luis [UNESP]; Panzavolta, Tiziana (Elsevier, 2020)
Lindgren funnel traps were used to monitor Pityophthorus juglandis occurrence. Traps were placed directly on walnut trees, with the top tied to one of the lower branches (about 2m high). An 8-funnel model was used instead of a 4-funnel trap, with the specific pheromone bait positioned between the fourth and the fifth funnel. Traps were customized with a 5mm metal mesh which was placed inside the bottom funnel so that debris (mainly foliage) and larger non-target insects would not end up inside the collecting jar. Geosmithia morbida was isolated from beetle adults, larvae and necrotic woody tissue around beetle galleries. Contaminant-free colonies were subcultured in purity and identified by: a) colony phenotyping [morphology, texture and pigmentation; margin type (regular/irregular; lobed/non-lobed); mycelium compactness; surface bumpiness; growth/temperature relationships]; b) micromorphology: type, morphology and ontogeny of conidiophores, metulae and phialides; conidiogenesis; shape, dimension and pigmentation of conidia; c) DNA fingerprinting. • Our protocol was customized to prevent traps from swinging in the wind and to optimize beetle catches by transversely fixing the bottom of funnel traps to the tree trunk with wooden shafts for stability. • To enhance fungus isolation in purity, a semi-selective Potato Dextrose Agar (PDA) medium, enriched with the antibiotics Ampicillin (Policillin-N) and Rifampicin (Rifamycin), was devised to prevent contamination by Gram-positive and Gram-negative bacteria and by mycobacteria.
Keywords: Ascomycete fungus; Bark beetle; Custom tools for WTB and GM surveillance and detection; Fungus isolation; Funnel traps; Macro-, micro-morphological features; Molecular identification; Quarantine organisms